Normative Vacuum in Indonesia’s Environmental Insurance Regulation: A Legal Certainty Analysis of Article 43 of Law No. 32/2009 and Government Regulation No. 46/2017 - Septiana, Anissa; Fadli , Moh.; Hadiyantina, Shinta (International Journal of Business, Law, and Education, 2026)
This article examines the legal certainty deficit in Indonesia’s environmental insurance regime by focusing on Law No. 32 of 2009 on Environmental Protection and Management (UUPPLH) and Government Regulation No. 46 of 2017 on Environmental Economic Instruments. Although Indonesian law formally recognizes environmental insurance as an environmental funding instrument, an environmental economic instrument, and a restoration guarantee, the implementing framework remains declarative, fragmented, and insufficiently operational. Using doctrinal legal research that combines statutory, conceptual, and case approaches, this study evaluates the regime through legal certainty theory, statutory formation theory, and normative delegation theory. The analysis identifies five critical deficiencies: undefined mandatory legal subjects, absence of indexed minimum coverage values, absence of standardized risk-based premium mechanisms, absence of definite claim submission and disbursement procedures, and absence of specific sanctions for non-compliance. Evidence from seven environmental pollution and land-fire cases adjudicated between 2021 and 2026 shows that environmental insurance has not functioned as an effective restoration-financing instrument; instead, compensation and restoration funding remain dependent on lengthy litigation and uncertain execution. The article argues that this failure is structural rather than merely technical because the parent statute and delegated regulations do not provide adequate substantive parameters for implementation. It recommends comprehensive reform through statutory clarification, an integrated Ministry of Environment–Financial Services Authority supervisory mechanism, and linkage of insurance obligations with OSS-RBA and AMDALNET licensing systems.